Antidiabetes Serbuk Umbi Tanaman Yakon (Smallanthus sonchifolius) pada Kadar Gula Darah Tikus Putih (Rattus norvegicus) - Thatit Nurmawati; Yeni Kartika Sari; Fina Ayu Ningtyas (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
The routine and long-term use of oral antidiabetic drugs in DM patients can make the public's perception worried about the side effects of the drug. In the Yakon (SS) plant tuber there is Fructooligosacaraide (FOS) which can reduce blood sugar levels. The research objective was to determine the effect of Yakon plant tubers on blood sugar levels in white rats with type 2 diabetes mellitus model. This type of research was experimental with a pre-post test design with control-group design. Independent variable, administration of Yakon plant tuber powder, dependent variable, blood glucose levels. The sample was divided into 2 groups (dose 1, dose 2) and a control group, each of 6 rats. The mice were given a high carbohydrate diet for 9 weeks. Treatment dose 1 (100 mg / kgBB) for 3 days. Measurement of blood sugar levels using Gluco-Dr. Data analysis used Paired Sample T-test, Independent Sample T-test, and One Way Anova. The results showed that the rats in the treatment group dose 1 experienced a decrease in the average blood sugar level of 122.83 mg / dl (p 0.002) (p 0.009). This shows that there is an effect of using Yakon plant tuber powder on blood sugar levels. The results of this study were the control group and the treatment group dose 1 (Sig. (2-tailed) = 0.000, Î± = 0.05). Meanwhile, the comparison results showed that there was a difference between the control group and the treatment group at dose 1, Based on the above research, Yakon tubers can be used to reduce blood sugar levels.